2020
DOI: 10.1002/adfm.202007016
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Powered Red/UV Narrowband Photodetector by Unbalanced Charge Carrier Transport Strategy

Abstract: Narrowband photodetector (NB‐PD) with selective light detection is critical for artificial vision and imaging. Intrinsic (optical‐filter‐free) NB‐PDs using conjugated organics or halide perovskite materials have been developed for eliminating the current complex filtering systems in NB‐PDs. However, the poor performance and external driving circuit of organic NB‐PDs as well as complex doping and uncontrollable recombination reactions in typical perovskite NB‐PDs have limited their applicational diversification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 77 publications
1
80
0
Order By: Relevance
“…Up to now, not only devices based on perovskite single crystals (PSCs) have been widely used but also perovskite films (PFs)-based devices have shown great potential for high-performance photodetectors for visible light, near-infrared light and high energy ray (Shao et al, 2014;Kim et al, 2017;Wang et al, 2018Wang et al, , 2020. For example, Kim et al (2017) used MAPbI 3 films for large-area, low-dose X-ray imaging, Ji et al (2018) reported OHIPs films-based photodetectors with highperformance and Hou et al (2020) reported narrowband photodetectors based on mixed halide PFs. The critical factors of PFs-based devices are high crystallinity, smooth morphology of films and good lattice matching between layers to form high-quality epitaxial films on substrates, which result in low trap density, long carrier lifetimes, and long diffusion lengths (Shi et al, 2015;Ji et al, 2018;Tang et al, 2019;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, not only devices based on perovskite single crystals (PSCs) have been widely used but also perovskite films (PFs)-based devices have shown great potential for high-performance photodetectors for visible light, near-infrared light and high energy ray (Shao et al, 2014;Kim et al, 2017;Wang et al, 2018Wang et al, , 2020. For example, Kim et al (2017) used MAPbI 3 films for large-area, low-dose X-ray imaging, Ji et al (2018) reported OHIPs films-based photodetectors with highperformance and Hou et al (2020) reported narrowband photodetectors based on mixed halide PFs. The critical factors of PFs-based devices are high crystallinity, smooth morphology of films and good lattice matching between layers to form high-quality epitaxial films on substrates, which result in low trap density, long carrier lifetimes, and long diffusion lengths (Shi et al, 2015;Ji et al, 2018;Tang et al, 2019;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the frequency range lower than 20 Hz, the i n of optimal narrowband PMOPDs is mainly dominated by flicker noise (1/f noise). In the frequency range higher than 20 Hz, i n approaches to shot noise limit (i s ), defined as i e I B = 2 s d , [45,46] as shown in the dash line in the inset of Figure 5b. The i n of the optimized narrowband PMOPDs is ≈4.3 × 10 −13 A Hz −1/2 at a frequency of 20 Hz.…”
Section: Resultsmentioning
confidence: 98%
“…This appearance of hysteresis loop and analog current change will be beneficial and an essential to mimic the bio-brain-like synaptic functionality. [5,6,[27][28][29] Based on the KPFM measurements, the tentative band alignment in metallic VO 2 phase is schematically illustrated in Figure S4, Supporting Information. To get insight into the Mott transition, the temperature-dependent resistance change (R-T) from 290 to 350 K with F = 5 µn (e.g., initial metallic state) with a tip (d = 120 µm) is measured (Figure 3f).…”
Section: Resultsmentioning
confidence: 99%